Expanding the structural repertoire of beta/alpha Ant-Pro (anthranilic acid-proline) oligomers into gamma/alpha 2-Amb-Pro (2-aminomethyl benzoic acid-proline) oligomers - Ramesh, Veera V. E.; Priya, Gowri; Rajamohanan, P. R.; Hofmann, Hans-Joerg; Sanjayan, Gangadhar J. (Tetrahedron, 2012)
In this article, we report a novel class of heterogeneous synthetic oligomers featuring the conformationally constrained amino acid residues - 2-aminomethyl benzoic acid (2-Amb) and proline (Pro) in repeating sequences. Oligomers as large as hexadecamers featuring the conformationally restricted gamma/alpha 2-Amb-Pro motif have been assembled using solution-phase Boc strategy, following multi-step synthetic sequences starting from the commercially available O-toluic acid. EDC-mediated peptide coupling has been found to be optimum for the assembly of the relatively non-polar oligomers, which could be readily purified by the standard column chromatographic purification procedures. This study offers considerable prospects of expanding the structural repertoire of beta/alpha Ant-Pro motif, which has been described earlier to assume right-handed helical architecture displaying robust nine-membered-ring closed network of hydrogen-bonding interactions, into gamma/alpha 2-Amb-Pro motif. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Amino acids; Foldamer; Peptides; Proline; Synthetic oligomers